2013
DOI: 10.1016/j.gloenvcha.2013.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Social influence approaches to encourage resource conservation: A meta-analysis

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
465
4
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 637 publications
(493 citation statements)
references
References 79 publications
15
465
4
9
Order By: Relevance
“…Wan et al [55] have suggested that public authorities should position "recycling as a social trend and promote it in the society through encouraging messages from the celebrity personalities and showing the percentage or frequency of the local population performing recycling". It can be a relevant approach in the context of recycling, as Abrahamese and Steg [82] perceived that "socially desirable behaviours could be achieved in issues related to resource conservation by means of social influences, learning and comparison". Wan et al [55] have also suggested that promoting recycling behaviour as a socially desirable trend instead of highlighting its benefits could be an effective strategy.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Wan et al [55] have suggested that public authorities should position "recycling as a social trend and promote it in the society through encouraging messages from the celebrity personalities and showing the percentage or frequency of the local population performing recycling". It can be a relevant approach in the context of recycling, as Abrahamese and Steg [82] perceived that "socially desirable behaviours could be achieved in issues related to resource conservation by means of social influences, learning and comparison". Wan et al [55] have also suggested that promoting recycling behaviour as a socially desirable trend instead of highlighting its benefits could be an effective strategy.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Studies tend to examine the immediate effects of interventions on behavior, but relatively few have provided follow-ups beyond a couple of weeks (e.g., Abrahamse & Steg, 2013;Staats et al, 2004). Consequently, understanding how to foster durable behavior change and embed new habits, while not a new topic, is relatively underexplored (Verplanken et al 1997;Bamberg, 2006).…”
Section: Consider the Practical Impacts Of Research (C) Understanmentioning
confidence: 99%
“…It has been reported that despite a proliferation of social influence approaches for behavior change, there is a lack of systematic research regarding the extent of their contribution and the conditions under which they are most effective [18]. More specifically, most intervention studies do not link the specific social influence mechanisms to the behavior changes, especially non-lab based ones [9], and there is a tendency for real-life interventions to contain several behavior change determinants, without further work to separate out the impacts [12].…”
Section: Volunteer Groupmentioning
confidence: 99%